The Influence of Transformational Leadership and Organizational Climate on Work Motivation and Innovative Work Behavior at the Department of Population and Civil Registration of East Lombok Regency - Salmun Rahman; Thatok Asmony; Siti Nurmayanti (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
Innovative work behavior plays a crucial role in creating and implementing valuable ideas for an organization. Leadership and organizational climate have a significant impact on supporting such behavior through support, facilitating creative thinking, providing resources, encouraging a culture of experimentation and learning, and setting an example of innovative behavior. The objective of this research is to analyze (1) the influence of transformational leadership on innovative work behavior, (2) the influence of organizational climate on innovative work behavior, (3) the influence of transformational leadership on work motivation, (4) the influence of organizational climate on work motivation, (5) the influence of work motivation on innovative work behavior, (6) the influence of transformational leadership on innovative work behavior through work motivation, and (7) the influence of organizational climate on innovative work behavior through work motivation. This study employs a quantitative associative method involving 132 employees as research participants. Data was collected using questionnaires and analyzed using SEM-PLS analysis. The research findings indicate that (1) transformational leadership does not have a significant influence on innovative work behavior, (2) organizational climate has a positive and significant influence on innovative work behavior, (3) transformational leadership has a positive and significant influence on work motivation, (4) organizational climate has a positive and significant influence on work motivation, (5) work motivation has a positive and significant influence on innovative work behavior, (6) transformational leadership has a significant influence on innovative work behavior through work motivation, and (7) organizational climate has a significant influence on innovative work behavior through work motivation.